PENGARUH FRAKSI MASSA SERAT DAUN NANAS DAN SERAT KACA TERHADAP KEKUATAN KOMPOSIT SEBAGAI MATERIAL ALTERNATIF BUMPER MOBIL - Lintang, Kemas Arif Ramadhan Lanang; Firdaus , Firdaus; Azharuddin, Azharuddin (MACHINERY Jurnal Teknologi Terapan, 2025)
In 2022, Indonesia produce 3.2 million tons of pineapples. Besides the fruit, pineapple leaves can be used as composite materials. Combining pineapple leaf fibers with glass fibers offers a potential high-strength material. This study examines how different mass fractions of these fibers affect composite strength for car bumper alternatives. The highest tensile strength (116.40 MPa) was found in a specimen with 18.52 g Pineapple Leaf Fiber, 43.89 g Glass Fiber, 38.70 g Epoxy, and 18.14 g Hardener. However, the T-test showed no significant effect of mass fraction on tensile strength (0.123 > 0.05). For flextural strength, the highest value (136.45 MPa) was in a specimen with 11.25 g Pineapple Leaf Fiber, 26.67 g Glass Fiber, 23.52 g Epoxy, and 11.02 g Hardener, with no significant effect of mass fraction (0.784 > 0.05). The highest impact strength (57.61 kJ/m²) was found in a specimen with 9.36 g Pineapple Leaf Fiber, 22.18 g Glass Fiber, 19.56 g Epoxy, and 9.17 g Hardener. Unlike the other tests, the mass fraction significantly affected impact strength (0.001 < 0.05).